The Effect of Project Manager’s Leadership Style on Performance of Water Projects in Kenya - Kariuki, James T. (European Scientific Journal, ESJ, 2018)
The objective of this study was to determine the relationship between project manager’s leadership style and performance of water projects in Kenya. Operationalization of leadership style was based on transformation and transaction leadership style while project performance was based on project time and cost performance. The study analyzed secondary and primary data for 102 water projects that were completed between 2011 and 2014. Hierarchical regression analysis was undertaken on the variables. The results show that a significant relationship exist between project manager’s leadership style and project time performance. In addition, the findings show that adoption of transformational leadership style leads to higher level of project performance. However, no significant relationship was established between project manager’s leadership style and project cost performance. This may be due to the use of fixed price contracts that specify the conditions for escalation and the maximum allowable cost escalations which could have made cost changes insignificant. The study has provided empirical evidence on the relationship between project manager’s leadership style and project performance within a developing country context. To enhance project time performance, project manager’s leadership style is critical and managers should strive to intellectually stimulate project team members.